Morphology of the favela in the North Zone of Rio de Janeiro: The relationship between formal urbanization and the growth of informality - Izaga, Fabiana (2023)
Based on a matrix of analysis developed in previous studies that identified four types of favelas in the city of Rio de Janeiro – enclave, line, block and mesh – this article seeks to deepen its study in five moments, over 100 years, from 1922 to 2022, in four communities in the Planning Area 3 (AP3), the North Zone, in the City of Rio de Janeiro. The approach is based on studies on the urban morphology of the contemporary city where the understanding of typomorphology is established as a synthesis of the relationships between urbanization processes and the conformation of the urban fabric. The methodology used in the analyses, which superimposes a formal and temporal approach, is based on the interpretation of changes in the urban fabric on maps from the official cartography of the City of Rio de Janeiro and satellite images available from Google. In the final considerations, we argue about the relationship that is established between formal urbanization and the form of informality growth and we verify the validity of typomorphological categories as a synthetic and diagrammatic approximation of the phenomenon of the favela in Rio de Janeiro.